BMP4 drives primed to naïve transition through PGC-like state - Shengyong Yu (Nature Communications, 2022)
Multiple pluripotent states have been described in mouse and human stem cells. Here the authors describe trajectories during BMP4 induced primed to naïve transition, which bifurcates into naïve and trophoblast-like branches with a PGC-like intermediate at the naïve branch.